Genetic Variation in Activity of Enzymes Involved in Synthesis of Catecholamines - Kessler, S. (1972)
A genetic analysis of differences in adrenal phenylethanolamine N-methyltransferase (EC 2.1.1.X) and tyrosine hydroxylase (EC 1.99.1.X.) and brain tyrosine hydroxylase was performed in three inbred mouse strains. In adrenal glands, the pattern of inheritance of both enzymes was similar; genes carried by the CBA/J strain appeared to be dominant to those of the other strains. The pattern of inheritance of tyrosine hydroxylase activity in adrenals differed from that in the brain. In both tissues, dominant genes appeared to determine intermediate, rather than extreme, levels of enzyme activities.